Short-term blood pressure variability in nondialysis chronic kidney disease patients: correlates and prognostic role on the progression of renal disease. Issue 12 (December 2018) - Borrelli, Silvio; Garofalo, Carlo; Mallamaci, Francesca; Tripepi, Giovanni; Stanzione, Giovanna; Provenzano, Michele; Conte, Giuseppe; De Nicola, Luca; Zoccali, Carmine; Minutolo, Roberto
Abstract : Objective: In chronic kidney disease (CKD), few cross-sectional studies evidenced an association between short-term BP variability (BPV) derived from ambulatory blood pressure (ABP) monitoring and renal damage. However, no study has evaluated the association of short-term BPV with the risk of CKD progression. Methods: We performed a cohort study to assess the correlates and the predictive value for incident renal outcomes of short-term BPV in hypertensive patients with CKD stage G1–5. As measures of short-term BPV, we considered the weighted SD (W-SD), and the coefficient of variation of SBP (CV-24-h SBP). Primary outcome was a composite endpoint of ESRD (chronic dialysis or transplantation) or GFR decline of at least 50%. Results: We included 465 patients (63.5 ± 14.2 years; 54.7% men; eGFR: 44 ± 22 ml/min per 1.73 m 2 ; proteinuria: 0.2 [0.1–0.9] g/day); W-SD, CV-24-h SBP and 24 h SBP were 12.5 ± 3.3 mmHg, 11.1 ± 2.8% and 127 ± 16 mmHg, respectively. W-SD was independently associated with older age, history of cardiovascular disease, diagnosis of diabetic, hypertensive and polycystic nephropathy, and higher 24 h SBP whereas no association with eGFR and proteinuria was found. During follow-up (median, 6.4 years), 130 patients reached the renal outcome (107 ESRD and 23 GFR decline of ≥50%). Higher 24 h, daytime and night-time SBP robustly predicted the composite renal endpoint [1.18 (1.10–1.25) for 5 mmHg], whereas BPV as measured by the W-SD did not either when expressed as a continuous variable [hazard ratio 0.97 (95% CI 0.91–1.04)] or when categorized into tertiles [1.16 (0.70–1.92) and 0.95 (0.54–1.68) in II and III tertiles, respectively]. Similar findings were found with CV-24-h SBP. Conclusion: In CKD patients, short-term BPV is strongly associated with 24 h, night-time and daytime BP but is independent from the eGFR and proteinuria and does not predict CKD progression.